Estimación de los parámetros de un modelo de pronóstico con componente cíclico con programación lineal - López Bello, Cesar Amilcar (Ingeniería, 2001)
The forecasting models with cyclic component are few treated, and the parameters estimations of those kind of models usually can be made with minims squares method. In this article is proposed the use of linear programming for made parameter estimation, in a forecasting model with cyclic component based in Fourier series, using as criteria the minimization of sum of absolute error. Finally, is make a comparative analysis of this technique, with, the minims squares method using simulating.